INNOVATION MANAGEMENT AND DIGITAL TRANSFORMATION IN THE TEXTILE INDUSTRY IN NAMANGAN REGION: CLUSTER MODEL AND EFFICIENCY MECHANISMS - Mamatqulov Eldor Nabijonovich (Ecomind Press, 2026)
This article analyzes innovative management models based on digital transformation and environmental sustainability in the textile industry of Uzbekistan. Using the example of textile clusters in the Namangan region, the possibility of increasing production efficiency by 25-30% through the use of vertical integration, AI-based forecasting systems, and Industry 4.0 technologies is studied. The study shows that by integrating circular economy models, bio-materials, and smart fabric technologies, it is possible to increase export volume to 5 billion US dollars by 2027 and increase product added value by 50%. The article provides recommendations for the establishment of innovative management institutions and the development of a digital ecosystem in the Namangan region, based on the experience of China (Zhejiang Province) and Turkey (Istanbul textile clusters).
Keywords: Textile innovations, digital transformation, Industry 4.0, vertical integration, bio-materials, circular economy, Namangan region, cluster management, investment efficiency.